OBJECTIVE AND SUBJECTIVE HEARING LOSS: FINDINGS FROM THE HISPANIC COMMUNITY HEALTH STUDY/STUDY OF LATINOS. (11th November 2018) - Arnold, M; Small, B J; Chisolm, T; McEvoy, C; Saunders, G; Bainbridge, K; Dhar, S; Hyer, K
Abstract: Numerous factors influence hearing aid use, including income, education, perceived need, and hearing loss, with perceived hearing loss and perceived need being the most robust predictors. However, most prior studies investigating hearing aid use have been conducted using predominantly White, non-Hispanic/Latino samples. It is not known whether predictors differ for adults from Hispanic/Latino backgrounds. This study describes the relationships between objective (measured pure tone average) and subjective (hearing handicap screening questionnaire) hearing loss among adults 45+ years in the Hispanic Community Health Study/Study of Latinos. Pearson r correlations demonstrated significant positive relationships between better-ear pure tone average and hearing handicap screening results. Findings suggest that adults from Hispanic/Latino backgrounds who have poorer measured hearing also report greater functional hearing-related handicap. Understanding the relationship between objectively measured hearing loss and subjective perceptions of hearing is a first step in identifying what factors predict hearing aid use among adults from Hispanic/Latino backgrounds.